Mechanochemical synthesis of corannulene-based curved nanographenes - Báti, Gábor (2023)
It is shown that corannulene-based strained π-surfaces can be obtained through the use of mechanochemical Suzuki and Scholl reactions. Besides being solvent-free, the mechanochemical synthesis is high-yielding, fast, and scalable. Therefore, gram-scale preparation can be carried out in a facile and sustainable manner. The synthesized nanographene structure carries positive (bowl-like) and negative (saddle-like) Gaussian curvatures and adopts an overall quasi-monkey saddle-type of geometry. In terms of properties, the non-planar surface exhibits a high electron affinity that was measured by cyclic voltammetry, with electrolysis and in situ UV/vis spectroscopy experiments indicating that the one-electron reduced state displays a long lifetime in solution. Overall, these results indicate the future potential of mechanochemistry in accessing synthetically challenging and functional curved π-systems.